Maritime security and law enforcement : the Malaysian experience - Su, Wai Mon (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2018)
Maritime security issue has been received the greater awareness by the international community since after the September 11 attack. Although there is no universal definition of the term 'maritime security', it covers a wide range of serious maritime security threats such as piracy and armed robbery at sea, maritime terrorism, threat of trafficking in arms and WMDs, threat of slavery, trafficking in persons and drug trafficking, IUU fishing, and threat of damage to marine environment which are of great concern for the international community. Not only the prescriptions of rules but also their effective enforcement is necessary for sustainable international maritime security. Port State jurisdiction has been found to be favoured by the international community as a response to the unreliable enforcement efforts by flag of convenience States particularly in cases of vessel-source pollution and illegal-fishing on the high seas. Coastguards are found to be the best models as law enforcement agencies as practiced by the United States, UK, Canada and Japan. The existing legal framework on maritime security in Malaysia is found to be insufficient because of legal loopholes particularly for maritime crime coverage since there is no substantive law to take action against serious maritime crimes such as piracy and maritime terrorism which leads to ineffective law enforcement. The evaluations on the maritime law enforcement mechanisms showed that Malaysia is in need of systematic national maritime security policy particularly in terms of distribution of powers to avoid overlapping jurisdiction among agencies in enforcing the laws. The critical appraisal of the MMEA evidences that the MMEA is yet to stand solely as the well-established agency for law enforcement against all maritime security threats because of its limited as well as very old assets which are almost 50 years old vessels and therefore, low efficient to perform law enforcement functions effectively. The comprehensive analysis of the MMEA Act 2004 reveals that there are weaknesses in the Act itself which need to be fixed to become clearer and more logical legislation particularly related to the issue of the right is 'hot pursuit'. There are various security threats challenging Malaysian maritime security where piracy and armed robbery at sea is found to be the most rampant. Other threats include maritime terrorism, security invasions in eastern coast of Sabah such as kidnapping for ransoms (KfR) and hijackings by terrorist groups, issue of unresolved maritime boundaries, human trafficking and smuggling of migrants, maritime environmental pollution and IUU fishing. These findings accentuate the need for sustainable legal and enforcement mechanisms in Malaysia.